She preached the word women's ordination in modern America - Knoll, Benjamin R. 1983-; Bolin, Cammie Jo 1994- (New York, NY Oxford University Press, 2018)
The need for a new perspective -- Women's ordination in America: a contemporary overview -- Support and skepticism regarding women's ordination -- Who supports women's ordination in America? -- A second look at views on women's ordination -- Clergywomen and young girls: the importance of role models -- The effect of clergywomen: religious representation -- The effect of clergywomen: religious empowerment and mobilization -- Clergywomen matter
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Ordination of women -- United States; Women in church work -- United States; Women clergy -- United States; Ordination of women -- United States; Women in church work -- United States; Women clergy -- United States; United States -- Church history; United States -- Church history